Mitochondrial oxidative stress impairs contractile function but paradoxically increases muscle mass via fibre branching. Issue 2 (1st February 2019) - Ahn, Bumsoo; Ranjit, Rojina; Premkumar, Pavithra; Pharaoh, Gavin; Piekarz, Katarzyna M.; Matsuzaki, Satoshi; Claflin, Dennis R.; Riddle, Kaitlyn; Judge, Jennifer; Bhaskaran, Shylesh; Satara Natarajan, Kavithalakshmi; Barboza, Erika; et al.
Abstract: Background: Excess reactive oxygen species (ROS) and muscle weakness occur in parallel in multiple pathological conditions. However, the causative role of skeletal muscle mitochondrial ROS (mtROS) on neuromuscular junction (NMJ) morphology and function and muscle weakness has not been directly investigated. Methods: We generated mice lacking skeletal muscle‐specific manganese‐superoxide dismutase (m Sod2 KO) to increase mtROS using a cre‐Lox approach driven by human skeletal actin. We determined primary functional parameters of skeletal muscle mitochondrial function (respiration, ROS, and calcium retention capacity) using permeabilized muscle fibres and isolated muscle mitochondria. We assessed contractile properties of isolated skeletal muscle using in situ and in vitro preparations and whole lumbrical muscles to elucidate the mechanisms of contractile dysfunction. Results: The m Sod2 KO mice, contrary to our prediction, exhibit a 10–15% increase in muscle mass associated with an 50% increase in central nuclei and 35% increase in branched fibres ( P < 0.05). Despite the increase in muscle mass of gastrocnemius and quadriceps, in situ sciatic nerve‐stimulated isometric maximum‐specific force ( N /cm 2 ), force per cross‐sectional area, is impaired by 60% and associated with increased NMJ fragmentation and size by 40% ( P < 0.05). Intrinsic alterations of components of the contractile machinery show elevated markers of oxidative stress, for example, lipid peroxidation is increased by 100%, oxidized glutathione is elevated by 50%, and oxidative modifications of myofibrillar proteins are increased by 30% ( P < 0.05). We also find an approximate 20% decrease in the intracellular calcium transient that is associated with specific force deficit. Excess superoxide generation from the mitochondrial complexes causes a deficiency of succinate dehydrogenase and reduced complex‐II‐mediated respiration and adenosine triphosphate generation rates leading to severe exercise intolerance ( 10 min vs. 2 h in wild type, P < 0.05). Conclusions: Increased skeletal muscle mtROS is sufficient to elicit NMJ disruption and contractile abnormalities, but not muscle atrophy, suggesting new roles for mitochondrial oxidative stress in maintenance of muscle mass through increased fibre branching.